2006
DOI: 10.1007/s00381-006-0198-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological pattern and frequency of intracranial tumors in children

Abstract: Males were affected more than females. A significant male predominance was observed in craniopharyngioma and medulloblastoma. Astrocytoma was the first most common brain tumor in all age groups. Certain tumor types show a predilection for the certain period of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
25
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 13 publications
13
25
3
Order By: Relevance
“…Tumor frequency was higher in the male pediatric population in the two first decades. This finding was in concordance with other studies (Ahmed et al, 2007;Mehrazin et al, 2007;Makino et al, 2010;Asirvatham et al, 2011). The main treatment of brain tumors is radiotherapy, and this is due to different factors like the inability of chemotherapy drugs to reach the brain and the technical difficulties involving surgery (Bock et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Tumor frequency was higher in the male pediatric population in the two first decades. This finding was in concordance with other studies (Ahmed et al, 2007;Mehrazin et al, 2007;Makino et al, 2010;Asirvatham et al, 2011). The main treatment of brain tumors is radiotherapy, and this is due to different factors like the inability of chemotherapy drugs to reach the brain and the technical difficulties involving surgery (Bock et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…In the infratentorial region, Medulloblastoma was observed in (40.6%), followed by cerebella astrocytoma (31.3%). Nayil found the most common tumour in the supratentorial and infratentorial compartments were craniopharyngioma and medulloblastoma respectively 16 , which support the current study.…”
Section: Discussionsupporting
confidence: 89%
“…Nayil et al found that 44.75% were supratentorial and 55.25% were infratentorial 17 . In another study, Ahmed et al showed supratentorial in 33.3% and infratentorial in 66.7% 16 . Headache, vomiting, visual disturbances, convulsion, neck stiffness and abnormal gait were found in both Supratentorial and Infratentorial brain tumours but no statistical significant (p<0.05) difference were found between them in this study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Brain tumors are the most common types of solid tumors in children, and they are reported to account for between 15% and 25% of all childhood malignancies [1][2][3]. Malignant Central nervous system tumors are the leading cause of mortality and morbidity in pediatrics compared to other types of cancers [4].…”
Section: Introductionmentioning
confidence: 99%